2005
DOI: 10.1242/jeb.01583
|View full text |Cite
|
Sign up to set email alerts
|

Physiological control of diving behaviour in the Weddell sealLeptonychotes weddelli: a model based on cardiorespiratory control theory

Abstract: Despite being obligate air breathers, many species of marine mammal are capable of spending most of their lives submerged in water. How they do this has been a subject of intense interest to physiologists for over a century, yet we still do not have a detailed understanding of the physiological mechanisms underlying this behaviour. What are the proximate mechanisms that trigger the 'decisions' to submerge and return to the surface? The present study proposes a model intended to address this question, based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…Moreover, some species of birds, at least, remove CO 2 in excess of the rate at which it is produced just before submerging, probably to ensure that high levels of CO 2 during submersion do not produce an urge to surface and breathe while there are still sufficient oxygen stores remaining (Halsey et al 2003a). A similar phenomenon has been proposed for Weddell seals (Stephenson 2005). In addition, birds in particular may spend varying periods of time at the surface engaged in other activities, such as preening.…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, some species of birds, at least, remove CO 2 in excess of the rate at which it is produced just before submerging, probably to ensure that high levels of CO 2 during submersion do not produce an urge to surface and breathe while there are still sufficient oxygen stores remaining (Halsey et al 2003a). A similar phenomenon has been proposed for Weddell seals (Stephenson 2005). In addition, birds in particular may spend varying periods of time at the surface engaged in other activities, such as preening.…”
Section: Discussionmentioning
confidence: 76%
“…End-of-apnea P CO 2 showed an increasing trend as apnea duration increased, varying between 49 and 70·mmHg, while pH fluctuated by less than 0.1 pH unit. In previous studies (Milsom et al, 1996;Stephenson, 2005), it has been suggested that CO 2 may play a primary role in the drive to breathe, but such investigations of respiratory control were beyond the scope of the present project. Our results serve only to demonstrate that end-of-apnea levels are variable in the blood and that there is no apparent threshold associated with the end of apnea.…”
Section: End Of Apnea and Hypoxemic Tolerancementioning
confidence: 90%
“…Oxidative metabolism during apnea, however, poses a challenge for CO 2 disposal. Excess CO 2 can alter respiratory drive as well as sleep structure (Milsom et al, 1996;Skinner and Milsom, 2004;Stephenson, 2005). Even though marine and terrestrial mammals have a similar hypercarbic chemosensitivity, the higher blood buffering capacity allows marine mammals to accommodate the CO 2 build-up…”
Section: Perspectives From Seal Apneamentioning
confidence: 99%